European integration and disintegration : East and West (Routledge, 1996)
Iz sadržaja: European security: a new era of crisis? ; The crisis in Italian state ; The Southern enlargement of the EC: Greece, Portugal and Spain ; Poland's 'return to Europe', 1989-94 ; French motives for European integration